Supply chain management practices, supplier performance and supply chain resilience in the South African public sector - Mugwenhi, Shephard (Vaal University of Technology, 2020)
The most important decisions that direct the operations of a nation are made in the public sector. The public sector performs the duty of facilitating the efficient and sustainable delivery of goods and services to the general public. In South Africa, public sector institutions have failed to fulfil their role of providing effective services, and this failure has been attributed to corruption and other inconsistencies inherent within supply chain management (SCM) transactions occurring between government and its suppliers. To streamline SCM, various legislative pieces such as the public SCM Policy Framework, the Preferential Procurement Policy Framework (PPPF) and the Broad-Based Black-Economic Empowerment (BBBEE) Act, among others were implemented in tandem with a host of other interventions. However, the challenges linked to public SCM continue to this day and the intended outcomes are yet to be fully realised, thereby negatively impacting on the effective delivery of services by the public sector. This study investigated the relationship between SCM practices, supplier performance and supply chain resilience in the South African public sector. The study is premised on the need to investigate how SCM practices may be applied to improve the effectiveness of supplier performance, and hence the resilience of the public supply chain in South Africa, in light of the numerous challenges faced by the sector. This study followed a quantitative method in which a cross-sectional survey was applied to collect data to test the relationships between seven SCM practices (supply chain collaboration, supply chain synergies, supply chain innovation, information sharing, information quality, supply chain design, supply chain integration), supplier performance and supply chain resilience. A structured survey questionnaire was developed using adapted measurement scales and administered to 333 SCM professionals recruited from public sector organisations based in the Gauteng Province. The data collected were analysed using the Statistical Package for Social Sciences (SPSS Version 25.0) and the Analysis of Moment Structures (AMOS Version 25.0) statistical software. The actual data analysis techniques applied included descriptive and inferential statistics and hypotheses were tested using structural equation modelling. The results of the study showed that three SCM practices, namely collaboration, innovation and integration exerted a significant positive influence on supplier performance. However, supply chain synergies, information quality and supply chain design were statistically insignificant. Moreover, information sharing exerted a significant negative influence on supplier performance. In turn, supplier performance exerted a significant positive influence on supply chain resilience. The study contributes in various ways to both public SCM theory and practice. Theoretically, it provides information on how the SCM dimensions considered in this study, which are supply chain collaboration, synergies, innovation, information sharing and quality, design, and integration are linked to supplier performance and supply chain resilience within the public sector in South Africa. Given the limited evidence of previous studies of this nature in the South African public sector, the results are an essential addition to the existing body of literature within the public SCM context in developing countries such as South Africa. From a managerial standpoint, the study provides information on which SCM practices deserve attention in the efforts to improve the performance of suppliers, and how the performance of suppliers can be harnessed to enhance the resilience of the public supply chain. Hence, the study offers an important diagnostic framework through which the SCM challenges facing the public supply chain in South Africa can be addressed.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supply chain management; Supply chain resilience; Public Sector; Supplier performance; Dissertations, Academic -- South Africa; Business logistics; Public administration -- South Africa